Walrasian Analysis via Strategic Outcome Functions - Schmeidler, David (Econometrica, 1980)
[This note provides a rigorous description of a game in a strategic form whose Nash equilibria are all strong equilibriaccoinciding with the Walras equilibria of the underlying Arrow-Breau pure exchange economy.]